2018
DOI: 10.1055/a-0593-5884
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic powder application for control of acute upper gastrointestinal bleeding in patients with gastric malignancy

Abstract: Background and study aims  Despite use of various endoscopic therapies in patients with tumor-related bleeding, various rates of successful immediate hemostasis and short-term rebleeding have been reported. We aimed to evaluate preliminary results of use of the EndoClot polysaccharide hemostatic system (PHS) in patients with acute upper gastrointestinal bleeding (UGIB) from a gastric malignancy. Patients and methods  We retrospectively analyzed data from a prospectively collected database of 12 patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Park et al 10 by propensity score matching, compared to the conventional endoscopic methods, found that there were no significant differences from the immediate hemostasis success rate of the 30 patients treated with EndoClot nor the incidence of rebleeding rate after 7 and 30 days. 11,12 However, Singh et al 13 conducted a study of hemostatic materials showing that the hemostatic success of commercially available microporous polysaccharide hemispheres was much lower than that of bovine-derived gelatin particles.…”
Section: Endoclotmentioning
confidence: 99%
“…Park et al 10 by propensity score matching, compared to the conventional endoscopic methods, found that there were no significant differences from the immediate hemostasis success rate of the 30 patients treated with EndoClot nor the incidence of rebleeding rate after 7 and 30 days. 11,12 However, Singh et al 13 conducted a study of hemostatic materials showing that the hemostatic success of commercially available microporous polysaccharide hemispheres was much lower than that of bovine-derived gelatin particles.…”
Section: Endoclotmentioning
confidence: 99%
“…Literature searches were conducted in PubMed databases published in English for the period since 2013 using related key words, such as ‘GC’, ‘bleeding’ and ‘endoscopic’ (Figure 1). We found five recent studies reporting on the outcomes of endoscopic therapy (ET) for GC bleeding [4,9,10,11,12] (Table 1) and a review article [13]. Four of these five reports were retrospective studies using conventional hemostatic modalities [4,9,10,11], whereas one prospectively investigated the suitability of hemostatic powder application as an initial endoscopic treatment modality [12].…”
Section: Endoscopic Management For Bleeding From Unresectable Gcmentioning
confidence: 99%
“…Previous studies reported a median overall survival (OS) and 30-day mortality rate of approximately 3–6 months and 0–22% after ET, respectively [4,9,10,11,12], although prognosis after ET depends on not only the efficacy of treatment but also tumor progression, the general condition, and concomitant therapy, such as chemotherapy and RT. Koh et al [9] found that the 30-day mortality rates in patients with successful and failed endoscopic hemostasis were 0% and 25.8%, respectively.…”
Section: Endoscopic Management For Bleeding From Unresectable Gcmentioning
confidence: 99%
See 2 more Smart Citations